"I don't want to have anything to do with someone suspected of COVID-19": a genuine infection avoidance interests or inappropriate concerns related to stigma? - Sulemana Abubakari; Edward Apraku; Solomon Nyame; Francis Agbokey; Samuel Afari-Asiedu; Stephaney Gyaase; Thomas Gyan; Lawrence Gyabaa Febir; Livesy Abokyi; Kwaku Poku Asante (AOSIS, 2023)
Background: Human existence is being challenged by an outbreak of coronavirus disease 2019 (COVID-19) caused by the virus SARS-CoV-2 that began in Wuhan, China in December 2019. Efforts to avoid the spread of COVID-19 are undermined by the appearance of disease-associated avoidance of infected persons due to reasons such as social stigma and discrimination. Objective: This study seeks to investigate avoidance and discrimination against persons suspected of COVID-19 in a predominantly rural setting in Ghana. Methods: The study is a cross-sectional survey. A random sample of 517 individuals drawn from a health and demographic surveillance system database was used for this study. Participants resided in six contiguous districts and municipalities of predominantly rural setting in the Bono East Region of Ghana. Results:  The findings showed that majority (60%) of the respondents agreed that they won't have anything to do with someone suspected of COVID-19. However, 67% of them were willing to accommodate persons that recovered from the infection. Majority (91%) of respondents agreed that there is a need to adopt tolerant attitude towards persons who recovered from the infection, whilst another 98% also reported the need to show compassion towards persons who recovered from COVID-19. Conclusion: There is a high-level avoidance of persons suspected of COVID-19, but little or no discrimination of those who recovered from the infection.